PENENTUAN KONSENTRASI HAMBAT MINIMUM (KHM) DARI EKSTRAK BUAH SAWO TERHADAP Salmonella typhi - Nurbaya, Siti; Silalahi, Yosy Cinthya Eriwaty; Nurussakinah, Nurussakinah; Purba, Trionaldo (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Sapodilla fruit (Manilkara zapota) belongs to the Sapotaceae family. Sapodilla fruit is traditionally used in traditional medicine to cure typhoid and sapodilla fruit is not only made medicine but also the sap is taken as raw material for making chewing gum. The purpose of the examination was to determine the minimum inhibitory concentration (MIC) of sapodilla fruit extract against Salmonella typhi bacteria. The method used is the agar diffusion method using Mueller Hinton Agar (MHA) as a growth medium and paper backing. The results of the examination of the effective inhibition at a concentration of 300mg/ml with a diameter of 15.4 mm while the minimum inhibitory concentration (MIC) was at a concentration of 50mg/ml against Salmonella typhi with the smallest inhibitory diameter of 11.5 mm. From the data above, sapodilla fruit extract has a great inhibitory power against Salmonella typhi